Tawhid Education in Overcoming Bullying Cases in Generation Z Adolescents: Prevention and Recovery Strategies - Munifah, Muthia; Salwa, Lugina Auliya; Fitri, Dina Riska; Siregar, Nur Indah; Safitri, Putri Anahar; Ainunnisa, Salsabila Rahma; Hidayat, Febryan (Solo Universal Journal of Islamic Education and Multiculturalism, 2024)
This study aims to analyze the design of appropriate prevention and recovery strategies by involving tawhid learning in cases of bullying that occur in Generation Z. The background of this study is the need for the right strategy to apply the understanding of tawhid in preventing bullying cases in the era of generation Z. The method used in this study is qualitative, with library research methods. Data was collected through literature studies and scientific papers of researchers who have been published as well as reviews of journals, articles, and scientific papers that can be trusted. The results showed that involving tawhid learning can minimize and prevent someone from bad behaviour including bullying behaviour. These findings indicate that applying monotheism learning can be an alternative method for preventing and stopping bullying cases that occur. This study concludes that applying tawhid learning in bullying prevention strategies can be a recommendation for educators and school administrators to consider the application of tawhid learning as an alternative method in preventing and stopping bullying cases that occur among Generation Z. This study has limitations on a limited sample of articles or journals under review and suggests for further research so that covers a wider and more diverse sample.